Engineering and product development management : - Armstrong, Stephen C. (Cambridge University Press, 2001)
Engineering and Product Development Management is a practical guide to the components of engineering management, using a holistic approach. It will help engineers and managers understand what they have to do to improve the product development process by deploying new technology and new methods of working in concurrent teams. The book takes elements from six well known and understood bodies of knowledge and integrates them into a holistic approach: integrated product development, project management, process management, systems engineering, product data management, and organizational change management. These elements are framed within an overall enterprise-wide architecture. The techniques discussed in this book work for both huge multinational organizations and smaller enterprises. The emphasis throughout is on practical tools which will be invaluable for engineers, managers, and consultants responsible for project and product development.